Предмет: Алгебра, автор: daniella25

Решите систему уравнений:


Приложения:

Ответы

Автор ответа: elinakhilko
1

Ответ:

(1;1)

Объяснение:

\left \{ {{log_{3}(2x+y)+log_{3}(2x-y)=1 } \atop {log_{3}(2x+y)-log_{3}(2x-y)=1}} \right.\\\left \{ {{log_{3}(4x^{2}-y^{2})=1  } \atop {log_{3}(\frac{2x+y}{2x-y} )=1}} \right.\\  \\\left \{ {{4x^{2}-y^{2}=3} \atop {\frac{2x+y}{2x-y}=3}} \right. =\left \{ {{4x^{2}-y^{2}=3} \atop {-4x+4y=0}} \right.=\left \{ {{4x^{2}-y^{2}=3} \atop {x=y}} \right. =\left \{ {{4y^{2}-y^{2}=3} \atop {x=y}} \right.=\left \{ {{x=1} \atop {y=1}} \right.

Автор ответа: m11m
1

Ответ:

Объяснение:

!!!!!!!!!!!!!!!!!!!!!!!!

Приложения:
Похожие вопросы
Предмет: Математика, автор: Аноним
Предмет: Математика, автор: Аноним